Devices and chemical sensing applications of metal oxide nanowires - Shen, Guozhen; Chen, Po-Chiang; Ryu, Koungmin; Zhou, Chongwu (Journal of materials chemistry, 2009)
Metal oxide nanowires, with special physical properties, are ideal building blocks for a wide range of nanoscale electronics, optoelectronics, and chemical sensing devices. This article will describe the state-of-the-art research activities in metal oxide nanowire applications. This paper consists of three main sections categorized by metal oxide nanowire synthesis, electronic and optoelectronic devices applications, and chemical sensing applications. Finally, we will conclude this review with some perspectives and outlook on the future developments in the metal oxide nanowire research area.